Serum PCSK9 Correlates with PTX3 and Apolipoproteins B, A1, and C3 Concentrations in Patients with Type 2 Diabetes - Małgorzata Waluś-Miarka; Maria Kapusta; Przemysław Miarka; Ewa Kawalec; Barbara Idzior-Waluś (Cardiovascular Therapeutics)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) is involved in the regulation of LDL metabolism. There is evidence that circulating PCSK9 is a cardiovascular risk factor. In this study, we determined factors associated with circulating PCSK9 in a group of patients with type 2 diabetes mellitus (DM2). Material included 116 consecutive patients with DM2 from outpatient diabetes clinic. Circulating PCSK9, PTX3, apolipoprotein (apo) B100, apo B48, and apo C3 levels were determined by ELISA, apo A1 by immunoturbidimetry. The mean (sd) age of patients was 59.1 (11.1) years, the mean (sd) values of serum PCSK9 were 255.4 (106.97) ng/ml. Circulating PCSK9 correlated negatively with age (r=−0.21, p<0.05) and HbA1c (r=−0.21, p<0.05) and positively with BMI (r=0.21, p<0.05), total cholesterol (r=0.59), LDL-cholesterol (r=0.50), triglyceride (r=0.35), apo B100 (r=0.43), apo A1 (r=0.43) (p<0.001 for all), apo C3 (r=0.29, p<0.01), and apo B48 (r=0.25, p<0.01) concentration and FLI (r=0.26, p<0.01). Strong correlation between PTX3 and PCSK9 levels was observed (r=0.47, p<0.001). Multiple stepwise backward regression analysis with PCSK9 as dependent variable revealed that PTX3, apo B100, apo A1, apo B48, and BMI were significantly positive and the presence of NAFLD and HbA1c negatively associated with PCSK9 concentrations. These variables together explain 57% of PCSK9 variability; the strongest relationship was observed between PCSK9 and PTX3 and apo B100. Our results indicate that circulating PCSK9 is significantly associated with inflammation marker PTX3 as well as atherogenic lipids and apolipoproteins C3, B100, and B48, which might be of value in understanding interactions between development of atherosclerosis and inflammatory state in DM2 patients.